Defensive pressure affects basketball technical actions but not the time-motion variables - Sampaio, J.; Leser, R.; Baca, A.; Calleja-Gonzalez, J.; Coutinho, D.; Goncalves, B.; Leite, N. (Journal of Sport and Health Science, 2016)
Background: Novel player tracking technologies can change the understanding of performance determinants in team sports by allowing to accurately measuring the activity demands. The aim of this study was to identify how the defensive pressure affects the time-motion variables and the technical actions in basketball. Methods: Twenty international male players (age: 16.05 ± 2.09 years, weight: 73.13 ± 8.10 kg, height: 183.10 ± 5.88 cm) played two 10 min basketball quarters, where they used a man-to-man 1/4-court defense until the 4th min (F1/4), changed to man-to-man full court (FULL) for 3 min and, from the 7th to the 10th min returned to 1/4-court defense (S1/4). A computerized notational analysis was performed using Simi Scout and positional data were captured with the Ubisense Real Time Location System (mean sampling rate 3.74 ± 0.45 Hz per transmitter/player). Results: The time-motion variables presented similar results between defensive conditions, showing a total distance covered around 90 m/min. However, results suggested possible vertical jump impairments in S1/4 periods. There was more distance covered while jogging in the offensive court (38.15 ± 12.17 m/min offensive court vs. 32.94 ± 10.84 m/min defensive court, p < 0.05) and more distance covered while running in the defensive court (16.41 ± 10.27 m/min offensive court vs. 19.56 ± 10.29 m/min defensive court, p < 0.05). Conclusion: These results suggest how to improve task representativeness during specific conditioning or game-based training situations and also to help coaches' strategic decisions during the games.